2006
DOI: 10.1001/archotol.132.1.12
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Positron Emission Tomography and Computed Tomography Fusion in the Management of Early-Stage and Advanced-Stage Primary Head and Neck Squamous Cell Carcinoma

Abstract: Objective: To evaluate the role of positron emission tomography and computed tomography (PET-CT) fusion in the management of early-stage and advanced-stage primary head and neck squamous cell cancer.Design: Retrospective analysis, with a blinded evaluation of clinical data and formation of a treatment plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 19 publications
0
44
1
10
Order By: Relevance
“…MR imaging provides superior soft-tissue delineation and better assessment of perineural (Fig 4) and bone marrow extension of the primary tumor. Although PET is highly accurate in the detection of primary tumor, 19,20 the resolution is inferior to CT and MR imaging in depicting the anatomic detail and the extent of the tumor that is essential for surgical planning. PET and PET/CT without contrast do not provide the anatomic detail sufficient for surgical planning purposes.…”
Section: T Stagementioning
confidence: 99%
“…MR imaging provides superior soft-tissue delineation and better assessment of perineural (Fig 4) and bone marrow extension of the primary tumor. Although PET is highly accurate in the detection of primary tumor, 19,20 the resolution is inferior to CT and MR imaging in depicting the anatomic detail and the extent of the tumor that is essential for surgical planning. PET and PET/CT without contrast do not provide the anatomic detail sufficient for surgical planning purposes.…”
Section: T Stagementioning
confidence: 99%
“…Similar studies have shown that PET/CT significantly alters TNM scores in patients with HNSCC by identifying nodal disease not apparent by CT, MRI, clinical exam, or combination thereof. Koshy and colleagues [20] found that PET/CT altered the TNM score in 36% of 36 patients compared with CT alone, while Ha and colleagues [21] found that PET/CT altered the TNM score in 31% of 36 patients compared with either CT or MRI. In both of these studies, 7 of the 36 patients (19%) had changes to their N status based on the information garnered from PET/CT but not identified on conventional imaging.…”
Section: N Stagementioning
confidence: 99%
“…However, the extent of nodal involvement was shown correctly by PET/CT only in nine of them. Two patients did not have the lymphatic nodes removed for histopathology examination [6].…”
Section: Discussionmentioning
confidence: 99%
“…PET offers new diagnostic possibilities as it supplements the morphological imaging with a functional view. Numerous studies have shown that PET is superior to CT in identifying primary lesions and metastases in patients with head-and-neck cancer [5,6]. A hybrid PET-CT can provide additional information by combining PET and CT images and create results with increased geometric accuracy.…”
mentioning
confidence: 99%